Legislation: Primary, Secondary and Tertiary - Burrows, John (Victoria University of Wellington Law Review, 2011)
This article considers the question of the delegation of lawmaking. The increasing use of tertiary legislation in New Zealand is analysed. It is suggested that the use of tertiary legislation is concerning in some aspects including the potential for abuses of power, inaccessibility, complexity and inconsistency.